Is there an app for that? Mobile phones and secondary prevention of cardiovascular disease. (September 2017) - Neubeck, Lis; Cartledge, Susie; Dawkes, Susan; Gallagher, Robyn
Abstract : Purpose of review: Advances in technology coupled with increased penetration of mobile phones and smart devices are rapidly changing healthcare delivery. Mobile phone applications ('apps'), text messages, and Internet platforms used alone or in combination are now providing interventions targeting people with multiple cardiovascular risk factors. The present article will review the emerging evidence regarding apps and discuss their potential role in providing secondary prevention interventions via mobile phones. Recent findings: Seven recent randomized controlled trials used text messages or apps for six to 12 months, with or without differing combinations of other technology platforms. All studies, involved cardiac and diabetes populations, and demonstrated at least one positive improvement to cardiovascular risk factor profiles. When measured, acceptability of the intervention was high. Summary: Mobile apps and technology can deliver positive outcomes in the management of cardiovascular risk factors. However, because of the complexity of combination interventions, it is difficult to determine the 'active' ingredient. A future challenge for researchers and clinicians will be to respond quickly to these rapidly evolving interventions in order to ensure the delivery of effective, evidence-based outcomes.